2023
DOI: 10.1002/ente.202301061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Air‐Cooling Performance of Lithium‐Ion‐Battery Module with Various Cell Arrangements

Rajesh Kumar,
Lalan Kumar Singh,
Anoop Kumar Gupta

Abstract: The significant heat generated during the operation of lithium‐ion batteries raises the battery temperature thereby leading to performance degradation and thermal runaway in a thermal abuse environment. Therefore, a simple but effective battery thermal management system (BTMS) is crucial to achieve the permissible operating temperatures. In this work, the performance of air‐cooled BTMS is evaluated by changing the arrangement of cells under discharging conditions. Seven distinct arrangements (trapezoidal, slan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Heat pipes and fins have been found to be effective cooling devices for BTMS [9][10][11][12][13][14][15][16][17]. Other approaches include using thermoelectric cooling techniques [18][19][20][21], manifold [22][23][24][25][26], cell arrangement [27], battery pack layout within the battery cabin [28], cooling channels [29][30][31][32][33], cold plates [34,35], and nanofluids [36][37][38][39]. On the other hand, Khateeb, et al [40], Duan and Naterer [41], Li, et al [42], and Wilke, et al [43] have experimentally confirmed that PCMs offer a significant improvement to BTMS.…”
Section: Introductionmentioning
confidence: 99%
“…Heat pipes and fins have been found to be effective cooling devices for BTMS [9][10][11][12][13][14][15][16][17]. Other approaches include using thermoelectric cooling techniques [18][19][20][21], manifold [22][23][24][25][26], cell arrangement [27], battery pack layout within the battery cabin [28], cooling channels [29][30][31][32][33], cold plates [34,35], and nanofluids [36][37][38][39]. On the other hand, Khateeb, et al [40], Duan and Naterer [41], Li, et al [42], and Wilke, et al [43] have experimentally confirmed that PCMs offer a significant improvement to BTMS.…”
Section: Introductionmentioning
confidence: 99%